The Relationship Between Coffee Consumption and Symptoms of Gastroesophageal Reflux Disease in Mulawarman University Students Hubungan Konsumsi Kopi Dengan Gejala Gastroesophageal Reflux Disease Pada Mahasiswa Universitas Mulawarman - Hafiedz, Adzan Fajar; Iskandar, Abdillah; Murti, Ignatia Sinta (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
GERD is a common disease suffered by people around the world, has clinical characteristics in the form of heartburn and gastric acid reflux. Coffee consumption is thought to have a strong relationship with the incidence of GERD. The purpose of this study was to determine the relationship between coffee consumption and symptoms of gastroesophageal reflux disease in Mulawarman University students. This study used a cross sectional approach and data collected using FFQ (food frequency questionnaire) and GERD-Q questionnaires to collect coffee consumption habits and GERD symptoms in research respondents. The population in this study were Mulawarman University students who were in coffee shops around Mulawarman University. The results obtained in this study are 66% of 97 respondents may not suffer from GERD and 72.2% of respondents often consume coffee. The test results of the relationship between coffee consumption and GERD symptoms using the chi-square test obtained a value of p = 0.571 (p>0.05). There is no correlation between coffee consumption and GERD symptoms in Mulawarman University students.